2020
DOI: 10.3390/jcm9113724
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Whole Exome Sequencing to Identify Rare but Remediable Neurologic Disorders

Abstract: Background: The aim of this study was to describe the application of whole exome sequencing (WES) in the accurate genetic diagnosis and personalized treatment of extremely rare neurogenetic disorders. Methods: From 2017 to 2019, children with neurodevelopmental symptoms were evaluated using WES in the pediatric neurology clinic and medical genetics center. The clinical presentation, laboratory findings including the genetic results from WES, and diagnosis-based treatment and outcomes of the four patients are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…A male patient (ID: 143) had maternal UPD 9 encompassing a region containing the VUS (Seo et al 2020 ). A male patient (ID: 71) with a homozygous variant in the PREPL gene responded to medical treatment after molecular diagnosis (Kim et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A male patient (ID: 143) had maternal UPD 9 encompassing a region containing the VUS (Seo et al 2020 ). A male patient (ID: 71) with a homozygous variant in the PREPL gene responded to medical treatment after molecular diagnosis (Kim et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ketogenic diet was started in a patient 159 with GLUT1 deficiency syndrome 1. Patient 71 and 363 with myasthenic syndrome, congenital, 22 and segawa syndrome, recessive received pyridostigmine and levodopa beginning at age 2.6 years and 10 months, respectively (Kim et al 2020 ). Patient 278 and 402 with urea cycle disorder were managed with low protein diet.…”
Section: Resultsmentioning
confidence: 99%
“…Variants were annotated, filtered and prioritized using software developed in-house, EVIDENCE (3bilion Inc, Seoul, South Korea). EVIDENCE incorporates daily automatically updated databases, variant classification schema based on the ACMG guidelines, and a symptom similarity scoring system as previously described ( Kim et al, 2020 ; Seo et al, 2020 ; Seo et al, 2022 ). All identified variants in this study were confirmed by Sanger sequencing and family study.…”
Section: Methodsmentioning
confidence: 99%
“…Since the advent of massively parallel, genomic-sequencing techniques in the early 2000s, the increased availability, reduced cost, and improved efficiency of next generation sequencing (NGS) have enhanced gene discovery for neurogenetic disorders and facilitated clinicians’ ability make accurate diagnoses ( Rexach et al, 2019 ; Kim et al, 2020 ). In particular, either whole exome sequencing (WES) or whole genome sequencing (WGS) can reveal more than 5,000 phenotypically and genetically diverse conditions with a single test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation